Энергетические аспекты пищевых нанотехнологий - Бурдо, О. Г.; Ряшко, Г. М.; Светличный, П. И. (НТУ "ХПИ", 2005)
The prospects of nanotechnology implementation in production of foodstuff were considered. The analysis of nanoprocess during pasteurization, drying, infusion and raw material concentrating was done. The estimation of power expenses at gradual introduction nanotechnologies and in different areas was carr ied out. Mechanisms and efficiency of nanotechnology are proved for low-temperature pasteurizations, drying, cryoco ncentrating, heat treatment of viscous products
Keywords: энергопотребление; энергия; энергообеспечение; пищевые технологии; термообработка сырья; сырье; пастеризация; концентрирование; экстрагирование; сушка; наномасштабные процессы